A Truthful Way to Live? Objectivity, Ethics and Psychoanalysis. (July 2019) - Lacewing, Michael
Abstract: Is there a best way to live? If so, is this a form of ethical life? The answer, I believe, turns on what we can say about the nature and place of the passions – emotions and desires – in our lives, including in particular, our ability to be truthful about our passions and our relations with other people. I approach the question through the work of Bernard Williams. I consider first what it might be for a way of life to be 'objectively' best, before looking more closely at the psychological conditions of such a life, using ideas from psychoanalysis on the way we hide our true passions from ourselves and the effect this can have on our understanding of both ourselves and others. I end by considering whether we can say that a truthful life is the best life, and whether it places universal and material constraints on how best to live.